CHARACTERIZATION OF THE IDENTITY OF PISCICULTURE IN THE HYDROGRAPHIC BASIN OF RIO BRANCO AND COLORADO - Cota, Thalitta Silva; Sccoti, Marta Silvana Volpato; Caramello, Nubia (Geosaberes; Vol 12 (2021), 2021)
A The research aimed to characterize the territorial identity of fish farming in the Hydrographic Basin of Branco and Colorado’s rivers in the state of Rondônia, identifying the productive organization and its territorial spatialization in 2008 and 2020. A semi-structured questionnaire was applied to fish farmers and identified through environmental licensing issued for distribution in the basin; the geostatistical kriging method was used to analyze the productive concentration. The time series presented a growth in tanks and area, going from 707 in 2008 to 2,441 in 2020. As for the installation of tanks, 60% of fish farmers use the pasture area and 40% the Permanent Preservation area. The most widely used crop system is the extensive one, with the major breeding of the species being the Colossoma macropomum . The main outlet is the State itself, where the production is traded at fairs, markets and slaughterhouses.